Impact of internal combustion engine overheating on lubricant oil degradation in a 2011 MAZDA bt50 vehicle - Montero Reyes, Yilena; Pilicita, Josué; Domínguez, Josué; Torresano, Carlos (Multidisciplinar (Montevideo), 2025)
Introduction: overheating of an internal combustion engine is a common problem that can cause deterioration of the lubricating oil, and overheating of internal combustion engines is a common problem in automobiles.Objective: to characterize aspects related to overheating of the internal combustion engine in a 2011 MAZDA bt50 vehicle.Method: a qualitative study was conducted to find out how overheating of an internal combustion engine affects the operation of radiators, coolant conductors and water conductors in a 2011 MAZDA bt50 vehicle.Results: it is important to note that engine temperature. An engine overheat can be harmful and lead to serious damage. Coolant is crucial to the cooling system. Many modern engines, including those of the Mazda BT-50, use multigrade oils. It is recommended to change the oil according to the recommended maintenance schedule.Conclusions: overheating of the combustion engine is a problem that significantly affects the operation of the engine, so proper maintenance is important, as well as an adequate cooling system to avoid power loss, increased fuel consumption and also overheating accelerates oil oxidation, loss of viscosity, formation of deposits and increased engine wear